Analysis Of The Effect Of Population Density, GRDP, Unemployment Rate, Government Expenditure, Minimum Wage, And The Proportion Of The Agricultural Sector’s GRDP On Poverty Level In West Java For The Period 2016-2021 - Dwi Rahayu Novianti; Yuni Prihadi Utomo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the effects of population density, Gross Regional Domestic Product (GRDP), the open unemployment rate, government expenditure, the regional minimum wage (RMW), and the proportion of the agricultural sector in GRDP on the poverty rate in West Java Province. The study employs panel data regression analysis, combining time series data from 2016 to 2021 and cross-sectional data from 27 regencies and cities in West Java. The estimation results indicate that the Fixed Effect Model (FEM) is the most appropriate model. The findings reveal that all variables in the model have a statistically significant impact on the poverty rate. Population density and the open unemployment rate have positive effects, indicating that increases in these variables are associated with higher poverty levels. In contrast, GRDP, government expenditure, and the proportion of the agricultural sector in GRDP have negative effects, suggesting that increases in these indicators contribute to poverty reduction. Although the regional minimum wage is theoretically expected to alleviate poverty, the results indicate a positive relationship between RMW and poverty. This may be attributed to its potential impact on the informal labor market or reduced employment opportunities. These findings provide important implications for poverty alleviation policies, particularly those that address demographic pressures, labor market dynamics, and the role of local economic sectors.